2021
DOI: 10.3389/fimmu.2021.803410
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Distinct Features of Immune Checkpoint Inhibitor-Related Myositis From Idiopathic Inflammatory Myositis: A Single-Center Experience With Systematic Literature Review and Meta-Analysis

Abstract: Immune checkpoint inhibitor (ICI)-related myositis is a rare, potentially fatal condition that warrants further studies. Its incidence, clinical features, and prognosis remain poorly understood. To address these gaps, we conducted a systematic review and meta-analysis to evaluate the risk of myositis associated with ICI for solid tumors by analyzing phase III randomized controlled trials of anti-programmed death-1/ligand-1 (PD-1/PD-L1) and anti-cytotoxic T-lymphocyte antigen-4 (CTLA-4). To complement this anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 109 publications
2
24
0
Order By: Relevance
“…The patients who died of the ICI myositis were significantly older and more likely to have ptosis than those who did not 15 . Most common causes of death were also different in patients with isolated ICI myositis and overlap myositis 16 . Among patients with isolated ICI myositis, the most common causes of death were cancer progression, followed by myositis and infection 16 .…”
Section: Disease Course and Outcomesmentioning
confidence: 95%
See 4 more Smart Citations
“…The patients who died of the ICI myositis were significantly older and more likely to have ptosis than those who did not 15 . Most common causes of death were also different in patients with isolated ICI myositis and overlap myositis 16 . Among patients with isolated ICI myositis, the most common causes of death were cancer progression, followed by myositis and infection 16 .…”
Section: Disease Course and Outcomesmentioning
confidence: 95%
“…A meta-analysis of 18 randomized clinical trials of various ICI regimens (n = 6838) showed an overall incidence as 0.38%. 16 The World Health Organization Pharmacovigilance Database with adverse drug reactions reported until February 2019 showed incidence of ICI myositis as 0.6%. 7 However, pharmacovigilance databases are often biased, skewing toward more serious manifestations and foregoing less serious ones.…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations